Trade, direct investment and production policies - Machinea, José Luis (UN SantiagoCL, 2006)
Analyzes the various links between trade and growth. Discusses the export dynamics of Latin America, the way in which the region has positioned itself within the international economy and the extent to which the region's capacity for growth is limited by that position. Analyses the role of FDI in growth and more specifically, its role in Latin America during the last decade.